Trophic ecology of syntopic anuran larvae, Rhinella arenarum (Anura: Bufonidae) and Hypsiboas cordobae (Anura: Hylidae): Its relation to the structure of periphyton - Pollo, Favio Ezequiel (2015)
The grazing of amphibian tadpoles has a significant effect on structure and function of freshwater algal communities. The aim of this study was to evaluate the composition of the diet, the amplitude and degree of overlap of the trophic niche of tadpoles of Rhinella arenarum and Hypsiboas cordobae. We captured tadpoles using nets in pond. Food items were identified to genus level and assigned to morphological guilds. The diet of both species consisted of microalgae, with a predominance of diatoms, but representatives of Cyanobacteria, Chlorophyta, Euglenozoa, Dinozoa and Ciliophora, were also recorded. A greater abundance was observed in H. cordobae diet, with diversity and richness showed significant differences between species. The proportion of individuals of each guild was different in the two species. As regards the size of the taxa consumed, both species consumed a higher proportion of small organisms. The differences in the diet of these species could be explained by different behaviors for food acquisition in the water column, as H. cordobae tends to be nektonic and R. arenarum benthic. The analysis of diets suggest that the quantity of food available to the tadpole anurans is very low; this could be due to water turbidity, depth, substrate type and strong variations in conductivity in a short period of time.